2018
DOI: 10.1080/21665095.2018.1486219
|View full text |Cite
|
Sign up to set email alerts
|

Transparency initiatives and Tanzania’s extractive industry governance

Abstract: The proper management of natural resources and its proceeds is critical for resource-rich countries. Many resource-rich countries have arguably been plagued by aspects of what scholars call 'the resource curse'. Overcoming 'the curse' has thus occupied center stage in studies about extractive resource governance. The Extractive Industries Transparency Initiative (EITI) has been promoted as having the potential to overcome some aspects of the resource curse especially the 'rentier politics'. Several countries h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Further research could investigate the conditions under which reflexivity does and does not happen, for example through an explanatory analysis of the evolving global EITI standard and the role of multi-stakeholder deliberations therein, or through (comparative) analyses of countries, including those that go beyond the narrow scope of the EITI (such as Norway, the Philippines and Tanzania, see e.g. EITI-International, 2021;EITI-Philippines, 2020;Poncian & Kigodi, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research could investigate the conditions under which reflexivity does and does not happen, for example through an explanatory analysis of the evolving global EITI standard and the role of multi-stakeholder deliberations therein, or through (comparative) analyses of countries, including those that go beyond the narrow scope of the EITI (such as Norway, the Philippines and Tanzania, see e.g. EITI-International, 2021;EITI-Philippines, 2020;Poncian & Kigodi, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The limited research that does focus on the effects of the EITI in addressing the negative impacts of extractive industries remains inconclusive. Some research has indicated that the EITI stimulates public debates (Magno & Gatmaytan, 2017), broader governance reform (Poncian & Kigodi, 2018), and discussions on and monitoring of environmental and social impacts (Vijge et al, 2019). Others indicate that deliberations within the MSG in some countries are insufficient to address the social and environmental impacts (Yanuardi et al, 2021) and that governments use the EITI merely as a legitimation tool (Aaronson, 2011; Furstenberg, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Many references discussed ambitious transnational governance mechanisms fomenting transparency as a basic value in governance and therefore also in mining performance (Poncian and Kigodi, 2018;Tissot, 2019), such as the Extractive Industry Transparency Initiative (EITI: Balag'kutu, 2017). Such discussions shed much light on the field, while at the same time leaving many grey areas, mainly due to lack of adaption to the SLO (Social Licence to Operate) and to historical, cultural and economic factors in specific contexts.…”
Section: Resultsmentioning
confidence: 99%
“…All activities associated with the natural gas extractions and production, from negotiation, contracting, to the signing of agreements should be open and transparent. However, in Tanzania, most of the contracts There are some efforts to deliver the information on natural gas development to the society, however, there are still difficulties in assessing information on some aspects of the natural gas sector such as contracts, agreement, revenues, operating costs, quality and value of the natural gas (Paasch, 2016;PCCB, 2012) Most contracts and agreements are written in English while the majority of local people speak Kiswahili and they are not apparent and open to the local communities (Kolumbia, 2017;Pedersen and Bofin, 2015;Poncian and Kigodi, 2018;TRREE, 2017) 2.…”
Section: Information On the Natural Gas Sectormentioning
confidence: 99%
“…Natural gas for the poverty alleviation Many people are optimistic believing that the gas discoveries would be a "positive impact" on their future generation (Twaweza, 2014) Survey of community participation and agreements are not open and transparent to the local communities (Kolumbia, 2017;Pedersen and Bofin, 2015;Poncian and Kigodi, 2018) and the companies which fail to comply on transparency and openness of their contracts and agreements should be banned from operating in the country (Moshi, 2013). For example, through the study conducted by PCCB (2012), many participants reported the difficulties in accessing the information on some aspects such as contracts, revenues, operation costs, employment opportunities, quantity, quality and value of natural gas, and investment potentials.…”
Section: The Use Of Natural Gas and Its Revenuesmentioning
confidence: 99%